If the Mind Doesn’t Know, the Eyes cannot See: A Case report of Localized Tetanus - Noor, Nawsabah; Hossain, Homayra Tahseen; Mohsin, Mohammad; Rishad, Mahbub Mayukh; Zahiruddin, Mohammad (Bangladesh Journal of Medicine, 2023)
Tetanus is a vaccine-preventable disease caused by a potent neurotoxin released by an obligate anaerobic bacterium, Clostridium tetani infection. Presentations of tetanus include generalized tetanus, neonatal tetanus, cephalic tetanus, and localized tetanus, the latter two being much rarer. This is a case report of localized tetanus involving the facial muscle in the form of lock jaw in 63-year inadequately immunized gentleman following an unhygienic tooth extraction from rural area. The condition deteriorated further, and the patient was under ventilatory support for 3days. The patient had antibiotics, antitetanus serum, sedatives, and wound care. The case is reported because of the rarity of localized tetanus, the diagnostic dilemma presented by the case, and the cultural interplay and understanding of the disease process by the patient/caregivers. It is also reported to highlight the gap in routine immunization and the need for booster doses in this age group. Successful management includes prompt diagnosis, neutralization of circulating toxin and elimination of C. tetani infection, control of spasms, maintenance of the airway, and management of respiratory failure and autonomic dysfunction. Bangladesh J Medicine 2023; 34(2): 168-170